2015
DOI: 10.3390/ma8125457
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Niobium Doping on the Electrical Properties of 0.4(Bi0.5K0.5)TiO3-0.6BiFeO3 Lead-Free Piezoelectric Ceramics

Abstract: Ceramics in the system (Bi0.5K0.5)TiO3-BiFeO3 have good electromechanical properties and temperature stability. However, the high conductivity inherent in BiFeO3-based ceramics complicates measurement of the ferroelectric properties. In the present work, doping with niobium (Nb) is carried out to reduce the conductivity of (Bi0.5K0.5)TiO3-BiFeO3. Powders of composition 0.4(K0.5Bi0.5)Ti1−xNbxO3-0.6BiFe1−xNbxO3 (x = 0, 0.01 and 0.03) are prepared by the mixed oxide method and sintered at 1050 °C for 1 h. The eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 45 publications
(68 reference statements)
1
4
0
Order By: Relevance
“…The low frequency data for ε' r and loss tangent are not shown as it is very noisy. As previously reported [15,43,[49][50][51], from the AC conductivity curves (Figure 4(c,f)), activation energies of 1.65 eV and 1.19 eV above ~600°C at the low frequency limit can be estimated for the single crystal and polycrystalline samples respectively (calculated from the data measured at 39.8 Hz) [52,53].…”
Section: Resultssupporting
confidence: 76%
“…The low frequency data for ε' r and loss tangent are not shown as it is very noisy. As previously reported [15,43,[49][50][51], from the AC conductivity curves (Figure 4(c,f)), activation energies of 1.65 eV and 1.19 eV above ~600°C at the low frequency limit can be estimated for the single crystal and polycrystalline samples respectively (calculated from the data measured at 39.8 Hz) [52,53].…”
Section: Resultssupporting
confidence: 76%
“…The leakage current density and ferroelectric polarization of the pellet shaped samples of bulk and nanoparticles were carried out using a ferroelectric loop tracer in conjunction with external amplifier (10 kV) (Marine India). [31,35]. During the solid sate synthesis of bulk undoped BiFeO 3 and cations substituted BiFeO 3 the formation of these secondary phases were observed in a number of previous investigations [31,[35][36][37].…”
Section: Methodsmentioning
confidence: 81%
“…[31,35]. During the solid sate synthesis of bulk undoped BiFeO 3 and cations substituted BiFeO 3 the formation of these secondary phases were observed in a number of previous investigations [31,[35][36][37]. In a previous investigation, it was observed that the specific reaction pathway has good influence on the final distribution of the secondary phases [38], however, the mechanism leading to the formation of those secondary phases is still unknown.…”
Section: Methodsmentioning
confidence: 97%
“…The presence of the triclinic Bi 4 O 7 (P-1 space group) and Ba 2 FeO 4 (P12/c1 space group) secondary phases were identified. These impurities emanate from the volatility of bismuth ions that were identified in doped BiFeO 3 materials [38,39]. To further analyze the substitution effect on structural properties, we executed a Rietveld refinement using FullProf software.…”
Section: Resultsmentioning
confidence: 99%